Comparison of Polydopamine-Coated Mesoporous Silica Nanorods and Spheres for the Delivery of Hydrophilic and Hydrophobic Anticancer Drugs - Pada, Anna-Karin (Int J Mol Sci, 2019)
Mesoporous silica nanoparticles (MSNs) have been widely studied as drug delivery systems in nanomedicine. Surface coating of MSNs have enabled them to perform efficiently in terms of bioavailability, biocompatibility, therapeutic efficacy and targeting capability. Recent studies have suggested the use of polydopamine (PDA) as a facilitative coating for MSNs that provides sustained and pH-responsive drug release, owing to the adhesive “molecular-glue” function of PDA. This further endows these hybrid MSN@PDA particles with the ability to carry large amounts of hydrophilic drugs. In this study, we expand the feasibility of this platform in terms of exploring its ability to also deliver hydrophobic drugs, as well as investigate the effect of particle shape on intracellular delivery of both a hydrophilic and hydrophobic anticancer drug. MSN@PDA loaded with doxorubicin (hydrophilic) and fingolimod (hydrophobic) was studied via a systematic in vitro approach (cellular internalization, intracellular drug distribution and cytotoxicity). To promote the cellular uptake of the MSN@PDA particles, they were further coated with a polyethylene imine (PEI)-polyethylene glycol (PEG) copolymer. Drug-loaded, copolymer-coated MSN@PDA showed effective cellular uptake, intracellular release and an amplified cytotoxic effect with both doxorubicin and fingolimod. Additionally, rods exhibited delayed intracellular drug release and superior intracellular uptake compared to spheres. Hence, the study provides an example of how the choice and design of drug delivery systems can be tuned by the need for performance, and confirms the PDA coating of MSNs as a useful drug delivery platform beyond hydrophilic drugs.